Contribution of thin films of ZrO2 on TiO2 nanotubes electrodes applied in the photoelectrocatalytic CO2 conversion - Perini, João A. Lima [UNESP]; Cardoso, Juliano C. [UNESP]; Brito, Juliana F. De [UNESP]; Zanoni, Maria V. Boldrin [UNESP] (Elsevier, 2018)
Zirconium dioxide (ZrO2) nanoparticles deposited on TiO2 nanotube (NT) surfaces (30nm of diameter) improved the photoelectrocatalytic conversion of carbon dioxide to fuel alcohol. The deposition of ZrO2 nanoparticles was performed by a wet chemical deposition method, which provided excellent interaction with the nanotubular catalyst, as confirmed by surface analysis techniques. Methanol (485μmolL-1) and ethanol (268μmolL-1) were the main products generated under optimized condition after 60min of the photoelectrochemical reduction of dissolved CO2 in 0.1mol L-1 Na2SO4 solution (pH 4.0) by Ti/TiO2NT-ZrO2 at -0.3V vs. Ag/AgCl (3.0molL-1 KCl), under irradiation from an Hg lamp (120mWcm-2). The ZrO2 deposits on Ti/TiO2NT electrode surface amplified the photocurrent around 282% in -0.7V, compared to Ti/TiO2NT, increasing methanol and ethanol formation by 1054 and 2934%, respectively, after 60min of the photoelectrocatalysis process. These results demonstrated the potential of using composites of Ti/TiO2NT-ZrO2 in photoelectrocatalytic reduction of dissolved CO2 and contribute to the development of efficient technologies for fuel production and the reduction of pollutants emissions to the environment.
Keywords: Adsorption; CO2 reduction; Methanol; Photoelectrocatalysis; Zirconia